Grid harmonic detection and system resonances indentification in wave power plant applications - Md Hasan, K.N. (2013)
There is a growing interest in electrical grid connection of single unit Wave Energy Converters (WECs), as well as the multiple units based Wave Power Plant (WPP) applications. Due to the increasing integration of high power converters in WPP, additional concerns on the harmonic current mitigation of WEC device arise which requires the grid filter installation. Furthermore, the identification and appropriate mitigation of additional harmonics at the WPP level is needed, as any inductances and capacitors of the WPP can interact with the resonant frequency of the entire system and lead to detrimental effects on equipment. The present paper focuses on the potential harmonic studies of a realistic proposed WPP layout, in which the system resonances are identified by performing the frequency scan and modal analysis (HRMA) methods. The later technique has the ability of determining the participation factor of each bus, finding in this way the nodes in the system that have more influence on the obtained results. In this way, the most suitable nodes in which additional filtering solutions should be implemented can be identified. Â© 2013 IEEE.